Managing cognitive impairment following stroke: protocol for a systematic review of non-randomised controlled studies of psychological interventions. Issue 1 (10th January 2018) - Merriman, Niamh A; Sexton, Eithne; Donnelly, Nora-Ann; McCabe, Grainne; Walsh, Mary E; Rohde, Daniela; Gorman, Ashleigh; Jeffares, Isabelle; Pender, Niall; Williams, David; Horgan, Frances; Doyle, Frank; et al.
Abstract : Introduction: Stroke is one of the primary causes of death and disability worldwide, leaving a considerable proportion of survivors with persistent cognitive and functional deficits. Despite the prevalence of poststroke cognitive impairment, there is no established treatment aimed at improving cognitive function following a stroke. Therefore, the aims of this systematic review are to identify psychological interventions intended to improve poststroke cognitive function and establish their efficacy. Methods and analysis: A systematic review of non-randomised controlled studies that investigated the efficacy of psychological interventions aimed at improving cognitive function in stroke survivors will be conducted. Electronic searches will be performed in the PubMed, Embase and PsycINFO databases, the search dating from the beginning of the index to February 2017. Reference lists of all identified relevant articles will be reviewed to identify additional studies not previously identified by the electronic search. Potential grey literature will be reviewed using Google Scholar. Titles and abstracts will be assessed for eligibility by one reviewer, with a random sample of 50% independently double-screened by second reviewers. Any discrepancies will be resolved through discussion, with referral to a third reviewer where necessary. Risk of bias will be assessed with the Risk of Bias in Non-randomized Studies of Interventions tool. Meta-analyses will be performed if studies are sufficiently homogeneous. This review will follow the Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement. The quality of the evidence regarding cognitive function will be assessed according to the Grading of Recommendations Assessment, Development and Evaluation. Ethics and dissemination: This systematic review will collect secondary data only and as such ethical approval is not required. Findings will be disseminated through presentations and peer-reviewed publication. This review will provide information on the effectiveness of psychological interventions for poststroke cognitive impairment, identifying which psychological interventions are effective for improving poststroke cognitive function. PROSPERO registration number: CRD42017069714.